2020
DOI: 10.21203/rs.3.rs-26391/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated serum levels of checkpoint molecules in patients with adult Still’s disease

Abstract: Background: The interaction between galectin-9 (Gal-9) and its ligand, T cell immunoglobulin and mucin-containing-molecule-3 (TIM-3), one of the coinhibitory receptors, transduce the inhibitory signaling to regulate immune responses. The dysregulated expression of checkpoint molecules has been reported under various inflammatory or autoimmune conditions. The aim of this study is to investigate the levels of these checkpoint molecules and their associations between proinflammatory markers in patients with adult… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Thus, various danger signals seem to be involved in the pathogenesis of AOSD. T cell immunoglobulin and mucin-containing-molecule-3 (TIM-3), an immune checkpoint molecule, was recently shown to control not only adaptive immunity but also innate immunity (50), and we reported that TIM-3 is significantly elevated in patients with AOSD (51). Nonetheless, due to the diversity of this immune checkpoint molecule's functions, further research is necessary to elucidate its role in AOSD.…”
Section: Pathogenesismentioning
confidence: 98%
“…Thus, various danger signals seem to be involved in the pathogenesis of AOSD. T cell immunoglobulin and mucin-containing-molecule-3 (TIM-3), an immune checkpoint molecule, was recently shown to control not only adaptive immunity but also innate immunity (50), and we reported that TIM-3 is significantly elevated in patients with AOSD (51). Nonetheless, due to the diversity of this immune checkpoint molecule's functions, further research is necessary to elucidate its role in AOSD.…”
Section: Pathogenesismentioning
confidence: 98%
“…These drugs affect membrane stability and alter transcriptional activity, leading to the inhibition of cytokine production and modulation of several co-stimulatory molecules (Schrezenmeier and Dorner, 2020). The anti-inflammatory or immunomodulatory effect may originate from a significant decrease in the production of cytokines, particularly pro-inflammatory factors including interleukin (IL)-6 and IL-1β (Ornstein and Sperber, 1996;Fujita et al, 2019).…”
Section: Mechanisms Of Therapeutic Actionmentioning
confidence: 99%